Consequences of the Chicago DSD Consensus: A Personal Perspective - Hughes, I. A. (Hormone and Metabolic Research, 2015)
A decade has passed since the Chicago Consensus meeting was convened to consider how to improve the management of individuals and their families with an intersex disorder. It is apposite to review, from an individual perspective, what impact the Consensus has had on clinical practice and research. Emphasis is placed on nomenclature and DSD classification, multidisciplinary team working, striving to reach a causative diagnosis for DSD, the value of uniformity of collective case registries for rare conditions, and the potential for meaningful clinical outcome studies and basic scientific research. The impact of the Consensus can be gauged objectively by an exponential increase in DSD-related publications in the medical and scientific literature and organisation of numerous national and international meetings. Psychologists and social scientists have embraced the subject area and enhanced the holistic approach to management of DSD. Much needs to be done to improve diagnosis, and to identify measures to predict outcome that can be used both in sex assignment decision-making and to improve the quality of life for young adults with DSD. Though challenging, these goals are attainable through specialist multidisciplinary clinics working at local level and the DSD community at large, collaborating at national and international levels to tap the data resources now being developed.
Keywords: DSD; nomenclature; diagnosis; multidiscipline